INFORMATION SYSTEM DEVELOPMENT GENERAL CRIME DATA MANAGEMENT KEDIRI CITY DISTRICT ATTORNEY - Ifrizul Hanif Muhammad; Teguh Andriyanto, Rini Indriati, Rina Firliana (ADISAM Publisher, 2022)
An information system is a combination of hardware, software, and users that form a system whose purpose is to receive data and process it into appropriate information for a particular purpose. A good information system, supported by accurate and secure data, improves the performance of every activity within the company, agency or institution and enables it to be carried out more effectively. The Kediri State Prosecutor's Office is one of the agencies engaged in the field of Community Service. One part of this agency that is important is case data, especially for the general crime section (Pidum). The General Crimes Section has the task of carrying out and controlling the handling of general criminal cases which include pre-prosecution, additional examination, prosecution, judge's determination and court decisions, supervision of the implementation of conditional crimes, supervision crimes, supervision of the implementation of parole decisions and other legal actions. The development of this information system uses the waterfall method which has several sequential stages, namely requirements analysis (Requirement Analysis), system design (System Design), implementation (Implementation), integration and testing (Integration & Testing), implementation and maintenance of the program (Operation & Maintenance). ). The result of the development of this information system is a web- based application called Smart Pidum which is a case data management application, especially in the general crime section. The development of the Smart Pidum information system can solve problems in managing case data and make it easier for officers to carry out their duties and responsibilities